Lexical features of diplomatic units found in the documents of the era of the Ottoman Empire (Journal of Oriental Studies, 2017)
History of diplomatic documents, written in Turkish, ancient. The lettersin the Turkish language, written in the distant past, have survived tothis day. The texts, written in the time of the Ottoman Empire, of sufficientquality, in the field of linguistic theory harmoniously structure compositionand grammatical base. The order of words in a sentence of the time savedin the modern Turkish language.The article discusses the diplomatic units, found in documents writtenduring the Ottoman Empire. Studied each diplomatic unit, the definitionof each word.